Analysis on the contribution of bKash to maintain the nation’s financial inclusiveness efforts and its demographical demand over the recent years - Momoshad, Shams Munawar (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.